An efficient mutagenesis system to improve the propamocarb tolerance in Lecanicillium lecanii (Zimmermann) Zare & Gams - Zhang, Yanjun; Zhang, Xiao; Qiu, Weiliang (Frontiers in Microbiology, 2023)
Lecanicillium lecanii (Zimmermann) Zare & Gams is used as an effective biopesticide for the control of sap-sucking insect pests on agricultural crops. However, low fungicide tolerance limits its large-scale field application. To improve the propamocarb tolerance in L. lecanii, a composite mutagenesis system was established by using UV-light (U), N-Methyl-N’-nitro-N-nitrosoguanidine (NTG) (N) and N+ ion-beam (I). The permutation type of three agents was a consecutive mutagenesis treatment (I/N/U) after an intermittent treatment (U+N+I). The “U” mutagenesis was performed at 254 nm for 60 s and at a distance of 45 cm under a 20 W germicidal lamp, the “N” mutagenesis was performed at a concentration of 1.0 mg/ml NTG for 60 min, and the “I” mutagenesis was performed by low energy N+ ion-beam using a dose of 10×1013 ions/cm2 at 30 keV. This composite mutagenesis system was recorded as the “U+N+I+I/N/U”, and then the mutagenesis efficiency in improving propamocarb tolerance was assessed by analyzing changes of mutants in the propamocarb sensitivity, mitotic stability, mycelial growth speed on plates or in liquid, sporulation on plates or aphids, conidial germination, 50% lethal concentration (LC50) and 50% lethal time (LT50) to aphids, lipid constituent and cell membrane permeability and control against aphids in the presence or absence of propamocarb. Compared to the wild-type isolate with a 50% effective concentration (EC50) value of 503.6 μg/ml propamocarb, the Ll-IC-UNI produced by the “U+N+I+I/N/U” had the highest EC50 value of 3576.4 μg/ml and a tolerance ratio of 7.1. The mutant was mitotically stable in 20-passage cultivation and did not show any unfavorable changes in growth and virulence indicators. The mutant showed the highest ability to resist or avoid the damaging effects of propamocarb as reflected by the alternations of lipid constituents and membrane permeability. The interval time for applying fungal agent was significantly shortened in this mutant after spraying a field recommended dose of 550 μg/ml propamocarb. In conclude, the “U+N+I+I/N/U” composite mutagenesis mode was efficient and useful to improve the propamocarb-tolerance of L. lecanii and the obtained Ll-IC-UNI could have commercial potential for field application.